Analisis Pengaruh Jumlah Produksi, Pendapatan Per Kapita, dan Nilai Kurs Terhadap Impor Kedelai di Indonesia - Melisa; Jafar, Rizka (ICOR: Journal of Regional Economics, 2024)
This study uses time series data from 2002 to 2021 to examine the variables that affect the amount of soybean imports to Indonesia. The method used is a quantitative method using multiple linear regression as an analytical tool. Secondary data was obtained by looking at statistical report data from the websites of Bank Indonesia, the Ministry of Agriculture, the Ministry of Trade and BPS. The dependent variable is the amount of soybean imports that enter Indonesia, while the independent variables are local soybean production, Indonesia’s per capita national income, and the exchange rate. The findings of this study indicate that the independent variable and the dependent variable are both significantly influenced by each other, which is indicated by a significance value that is smaller than the probability (0.000006 > 0.05), which supports this conclusion. Partially, the amount of domestic soybean production has a quite large negative impact and per capita income has a significant positive effect on the amount of soybean imports in Indonesia; but the exchange rate variable has a negligible link to the volume of soybean imports in Indonesia.